(3CfSGH GdCTQGa hCNHGQges - (3CHh GdMSf CMeO Hf jMji Hf LGHQ Hf OGhO, GdHdGPQj,J (B279 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO CKfGA eGOI eG bHd YfhGf (B" (3ebJd GdfYeGf Hf HTjQ Hf SYO Hf KYdHI ef Hfi GdMGQK (B" (3, bhdg (B" (3GdeOGFfi Yf eSdeI Hf eMGQH Yf CHjg (B: (3Cf eQhGf ZRG Cgd eYTQ aGeJfYhG efg hJMUfhG abGJdge MJi XgQ Ydjge s
(3BNQgG (B:s
(3ef YfhGf (B" (3HjYI GdhdjO hSdjeGf hNdY GHf YHO GdYRjR (B" (3, bhdg (B" (3bGdhG (B: (3hdeG CNQL YHO Gdedc EMJRe GdhdjO heTi Hjf jOi SQjQg f hcGf ai WQjbge Edi GdebGHQ ai CjGe YHO Gdedc , hhdGjI GdMLGO Hf jhSa Hf GdMce Hf CHj Ybjd G GdYQGb s
(3ef GdfSNI GdChdi faSgGs
(3gPg GdfSNI UhQJ Yf OGQ GdcJH GdeUQjI JMJ Qbe (B1103 (3JGQjN hgj Yf fSNI YGTQ CafOi HESJfGHhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B267s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B147 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B216 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B179s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs